Divergence of AMP Deaminase in the Ice Worm Mesenchytraeus solifugus (Annelida, Clitellata, Enchytraeidae). (16th June 2009) - Marotta, Roberto; Parry, Bradley R.; Shain, Daniel H.
Abstract : Glacier ice worms, Mesenchytraeus solifugus and related species, are the largest glacially obligate metazoans. As one component of cold temperature adaptation, ice worms maintain atypically high energy levels in an apparent mechanism to offset cold temperature-induced lethargy and death. To explore this observation at a mechanistic level, we considered the putative contribution of5 ′ adenosine monophosphate deaminase (AMPD), a key regulator of energy metabolism in eukaryotes. We cloned cDNAs encoding ice worm AMPD, generating a fragment encoding 543 amino acids that included a short N-terminal region and complete C-terminal catalytic domain. The predicted ice worm AMPD amino acid sequence displayed conservation with homologues from other mesophilic eukaryotes with notable exceptions. In particular, an ice worm-specific K188E substitution proximal to the AMP binding site likely alters the architecture of the active site and negatively affects the enzyme's activity. Paradoxically, this would contribute to elevated intracellular ATP levels, which appears to be a signature of cold adapted taxa.